Pengaruh Digital Transformation, Innovation Capability, dan Organizational Agility Terhadap Organizational Resilience pada UMKM Fashion Muslim - Ardina Ruri Reswari Siregar; Reny Nadlifatin (SENTRI: Jurnal Riset Ilmiah, 2026)
Muslim fashion SMEs play a strategic role in Indonesia’s economy but face substantial challenges due to changing trends, intense competition, and shifts in consumer behavior, including showrooming and webrooming phenomena. These circumstances require strong organizational resilience to sustain business continuity. This study aims to analyze the influence of digital transformation, innovation capability, and organizational agility on organizational resilience in Muslim fashion SMEs in the Tanah Abang area. A quantitative approach was employed, involving a survey of 150 SME owners and managers, with data analyzed using the PLS-SEM method. The findings indicate that digital transformation and innovation capability have a positive and significant effect on organizational resilience. Digital transformation enhances operational efficiency and market adaptability, while innovation capability promotes the renewal of products and business models relevant to the Muslim fashion industry. Conversely, organizational agility does not have a significant effect, suggesting that organizational agility alone is insufficient to strengthen resilience without adequate support from digitalization and innovation. This study provides practical implications for enhancing the competitiveness and resilience of Muslim fashion SMEs in increasingly dynamic market conditions.